Antiaging Mechanism of Natural Plant Sources: A Potential Current Product - Nafissa, Naja; Isnaini, Nadia; Desiyana, Lydia Septa; Prajaputra, Vicky; Harnelly, Essy; Zulkarnain, Zulkarnain; Maryam, Siti (Journal of Patchouli and Essential Oil Products, 2023)
The aging process is a multifaceted phenomenon influenced by various intrinsic and extrinsic factors. Oxidative stress, stemming from an imbalance between intracellular antioxidants and the excessive production of reactive oxygen species, is known to accelerate aging. Skin aging manifests through wrinkles, fine lines, and dark spots that become visible on the skin's surface. In modern times, cosmetics are not just associated with beauty but also with achieving younger-looking skin. There is a growing demand for anti-aging cosmetics formulated with natural ingredients. Natural anti-aging ingredients, such as plant extracts and antioxidants, including secondary compounds like phenols, flavonoids, alkaloids, tannins, anthocyanins, and coumarins, have gained popularity due to their potential to counteract the effects of oxidative stress and inflammation. These compounds play a pivotal role in neutralizing free radicals, oxidative stress, promoting collagen and skin elasticity, as well as addressing pigmentation and serving as natural skin-whitening agents. This research aims to explore the anti-aging mechanism of natural lant sources in making potential cosmetic Products.Keywords:antiaging, cosmetics, natural cosmetics, mechanism natural cosmetics